Project management as a current trend in modern management (on the example of the education sector) (Acta Education, 2024)
This article discusses the significance of project management as a distinct field of management science. With rapid changes occurring in various sectors, project management has become increasingly important. Using the example of analyzing the significance of project management in education, the article examines various methods and techniques. Based on this analysis, the importance and significance of project management in education is justified.